2017
DOI: 10.1038/aps.2017.93
|View full text |Cite
|
Sign up to set email alerts
|

Barbaloin inhibits ventricular arrhythmias in rabbits by modulating voltage-gated ion channels

Abstract: Barbaloin (10-β-D-glucopyranosyl-1,8-dihydroxy-3-(hydroxymethyl)-9(10H)-anthracenone) is extracted from the aloe plant and has been reported to have anti-inflammatory, antitumor, antibacterial, and other biological activities. Here, we investigated the effects of barbaloin on cardiac electrophysiology, which has not been reported thus far. Cardiac action potentials (APs) and ionic currents were recorded in isolated rabbit ventricular myocytes using whole-cell patch-clamp technique. Additionally, the antiarrhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Barbaloin (Bar), the primary active ingredient in aloe has gained increasing attention (21). A recent study has demonstrated that Bar controls ventricular arrhythmia by regulating voltage-gated ion channels (22). Bar pretreatment inhibits myocardial oxidative stress by activating the AMP-activated protein kinase (AMPK) signaling pathway, thereby alleviating MIRI (23).…”
Section: Introductionmentioning
confidence: 99%
“…Barbaloin (Bar), the primary active ingredient in aloe has gained increasing attention (21). A recent study has demonstrated that Bar controls ventricular arrhythmia by regulating voltage-gated ion channels (22). Bar pretreatment inhibits myocardial oxidative stress by activating the AMP-activated protein kinase (AMPK) signaling pathway, thereby alleviating MIRI (23).…”
Section: Introductionmentioning
confidence: 99%
“…The meanings of all variables were identical to the previous descriptions [14]. As is shown in Figure 2, SH exerted various effects on I Na.P steady state inactivation and steady state activation (Fig.…”
Section: Effects Of Sh On Steady State Activation and Inactivation Ofmentioning
confidence: 85%
“…85-23). Rabbit ventricular cardiomyocytes were isolated enzymatically, as described previously [14]. In brief, medium-sized adult New Zealand white rabbits of either sex were anesthetized with ketamine (Fujian Gutian Pharmaceutical Co., Ltd., Gutian, Fujian, China, 30 mg/kg i.v.)…”
Section: Isolation Of Ventricular Myocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, barbaloin dose-dependently blocked I Ca-L and in Langendorff mounted hearts significantly inhibited aconitine-induced ventricular arrhythmias. 59 It is reported that Aloe vera may increase the chance of hypokalemia and causing digitalis toxicity and arrhythmia. 23 …”
Section: Plants and Their Ingredients With Antiarhythmic Propertiesmentioning
confidence: 99%